Growth to Grit: The Role of Growth Mindset In Grit Among Students Who Are Active in The Student Council - Setyawan, Yonathan; Aryono, Marcella Mariska (Psikoborneo: Jurnal Ilmiah Psikologi, 2025)
The Student Council (OSIS) is a forum for high school/vocational school students to develop soft skills and character building, but often students who are actively involved in the Student Council do not understand its meaning and lack persistence in carrying out each program activity that is held. This study aims to examine the role of growth mindset on grit among high school/vocational school student council members in Madiun City. The sample consisted of 70 students from high schools/vocational schools in Madiun City. The data collection tools used were the growth mindset scale developed by Dweck, C.S. (1999) and the grit scale developed by Duckworth (2009). The analysis technique used in this study was regression analysis. The results showed that there was an effect of growth mindset on grit (t = 4.715, p = 0.033). The effective contribution of growth mindset to grit was 65%, while the remaining 35% was influenced by other factors not explored in this study. This study supports the theory that growth mindset influences grit. These findings can be used as a basis for developing an intervention model aimed at increasing grit in students who are active in student council organizations.OSIS merupakan wadah bagi siswa SMA/SMK untuk pengembangan soft skill dan pembentukan karakter, namun kerapkali siswa yang terlibat aktif dalam OSIS belum memaknai dan kurang gigih dalam melaksanakan setiap program kegiatan yang di adakan. Penelitian ini bertujuan untuk melihat peran growth mindset terhadap grit pada siswa OSIS SMA/SMK di Kota Madiun. Sampel terdiri dari 70 siswa dari SMA/SMK di Kota Madiun. Alat pengumpulan data yang digunakan adalah skala growth mindset yang dikembangkan oleh Dweck, C.S. (1999) dan skala grit yang dikembangkan oleh Duckworth (2009). Teknik analisis yang digunakan dalam penelitian ini adalah analisis regresi. Hasil penelitian menunjukkan bahwa terdapat pengaruh growth mindset terhadap grit (t = 4.715, p = 0.033). Besar sumbangan efektif growth mindset terhadap grit adalah 65%, sementara 35% sisanya dipengaruhi oleh faktor lain yang tidak dieksplorasi dalam penelitian ini.  Penelitian ini mendukung teori bahwa growth mindset mempengaruhi grit.  Temuan ini dapat dijadikan dasar untuk mengembangkan model intervensi yang bertujuan untuk meningkatkan grit pada siswa yang aktif berorganisasi OSIS.